2003
DOI: 10.1097/00005176-200301000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Probiotic Therapy in Acute, Severe Dehydrating Diarrhea

Abstract: Our data implies that colonization must occur before benefits of probiotics can be realized. Probiotics are, therefore, likely to be of limited benefit in treating diarrheal illnesses of short duration such as viral enteritis. The beneficial effects of probiotics may be limited to prophylactic usage in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 14 publications
(11 reference statements)
1
54
0
7
Order By: Relevance
“…18 In Brazil, a study including 124 children was carried out to assess the effect of Lactobacillus GG on the reduction of fecal losses in children with severe acute diarrhea associated with dehydration (moderate or severe in over 90% of patients). 19 The mean duration of diarrhea right after the intervention was similar (p = 0.59), 38.3±3.8 and 39.1±4.6 hours, respectively, in the groups that received probiotic and placebo. In addition, fecal losses varied considerably in both groups, with similar medians (p = 0.81), 67.7 and 56.1 mL/kg, respectively, in the probiotic and placebo groups.…”
Section: Probiotics and Diarrheamentioning
confidence: 82%
See 1 more Smart Citation
“…18 In Brazil, a study including 124 children was carried out to assess the effect of Lactobacillus GG on the reduction of fecal losses in children with severe acute diarrhea associated with dehydration (moderate or severe in over 90% of patients). 19 The mean duration of diarrhea right after the intervention was similar (p = 0.59), 38.3±3.8 and 39.1±4.6 hours, respectively, in the groups that received probiotic and placebo. In addition, fecal losses varied considerably in both groups, with similar medians (p = 0.81), 67.7 and 56.1 mL/kg, respectively, in the probiotic and placebo groups.…”
Section: Probiotics and Diarrheamentioning
confidence: 82%
“…In addition, fecal losses varied considerably in both groups, with similar medians (p = 0.81), 67.7 and 56.1 mL/kg, respectively, in the probiotic and placebo groups. 19 A study conducted in Bangladesh assessed the effect of Lactobacillus paracasei in 230 male infants aged 6 to 24 months and with diarrhea for less than 2 days. The study showed that the use of probiotics was associated with a statistically significant reduction in the following parameters of patients with nonrotavirus diarrhea: cumulative fecal loss, number of bowel movements, intake of oral rehydration solution and proportion of children whose diarrhea resolved on the sixth day of intervention.…”
Section: Probiotics and Diarrheamentioning
confidence: 99%
“…This probiotic is able to decrease the excretion of rotavirus in the stool [58], helping to reduce the spread of the virus, in turn improving the effectiveness of preventive strategies both in communities and during hospitalization. Yet, definitive conclusions cannot be drawn based on the available results [59][60][61]. The effectiveness of treatment with probiotics is demonstrated in mild-to moderateseverity rotavirus gastroenteritis, while the results obtained in the treatment of rotavirus negative forms and, especially, in bacterial infections are inconclusive [54,61].…”
Section: Infectious Gastroenteritismentioning
confidence: 99%
“…Favorable effects of probiotics are well documented in children with acute diarrheal infections, especially of viral etiology. These conditions were most frequently treated with Lactobacillus GG, L. plantarum and L. casei Shirota, some strains of bifidobacteria, and Streptococcus thermophilus [123][124][125][126][127]. E. coli Nissle 1917 and another nonpathogenic E. coli strain (O83:K24:H1) prevented diarrhea in sucklings and preterm newborns [56,128].…”
Section: Infectious Enterocolitismentioning
confidence: 99%